Language and religion - Yelle, Robert A.; Handman, Courtney, 1975-; Lehrich, Christopher I. (Language intersections ;, 2019)
The volumes in this series include current research on the debates at the intersection of linguistics and a range of sciences, social sciences and humanities fields, including health, business, law, and music. Each volume includes research from both sides of the fields covered, ensuring clear discussions about terminological divides, shared and differing approaches, as well as varying and similar bodies of literature